Enantioselective Synthesis of (–)-Pentazocine and (–)-Metazocine - Hu, Lin; Zhang, Lihe; Zhai, Hongbin (Synlett, 2016)
We have accomplished an efficient asymmetric synthesis of (–)-pentazocine and (–)-metazocine from the readily available d-tyrosine, featuring a ring-closing metathesis (RCM) reaction for the formation of the C ring and an intramolecular Friedel–Crafts reaction for the assembly of the B ring. The new strategy established herein should be applicable to enantioselective synthesis of a broad range of chiral benzomorphan analogues, thereby facilitating the biological and medicinal chemistry studies of these clinically important molecules.
Keywords: benzomorphans; pentazocine; metazocine; asymmetric synthesis; ring-closing metathesis reaction